Metformin Attenuates Neutrophil Recruitment through the H3K18 Lactylation/Reactive Oxygen Species Pathway in Zebrafish - Ren Zhou; Rui-Chen Ding; Qian Yu; Cheng-Zeng Qiu; Hao-Yi Zhang; Zong-Jun Yin; Da-Long Ren (Antioxidants, 2024)
Beyond its well-established role in diabetes management, metformin has gained attention as a promising therapeutic for inflammation-related diseases, largely due to its antioxidant capabilities. However, the mechanistic underpinnings of this effect remain elusive. Using in vivo zebrafish models of inflammation, we explored the impact of metformin on neutrophil recruitment and the underlying mechanisms involved. Our data indicate that metformin reduces histone (H3K18) lactylation, leading to the decreased production of reactive oxygen species (ROS) and a muted neutrophil response to both caudal fin injury and otic vesicle inflammation. To investigate the precise mechanisms through which metformin modulates neutrophil migration via ROS and H3K18 lactylation, we meticulously established the correlation between metformin-induced suppression of H3K18 lactylation and ROS levels. Through supplementary experiments involving the restoration of lactate and ROS, our findings demonstrated that elevated levels of both lactate and ROS significantly promoted the inflammatory response in zebrafish. Collectively, our study illuminates previously unexplored avenues of metformin’s antioxidant and anti-inflammatory actions through the downregulation of H3K18 lactylation and ROS production, highlighting the crucial role of epigenetic regulation in inflammation and pointing to metformin’s potential in treating inflammation-associated conditions.